Hub Long Noncoding RNAs with m6A Modification for Signatures and Prognostic Values in Kidney Renal Clear Cell Carcinoma - Lin, Gaoteng; Wang, Huadong; Wu, Yuqi; Wang, Keruo; Li, Gang (Frontiers in Molecular Biosciences, 2021)
Background: N6-methyladenosine (m6A)-modified long noncoding RNAs (m6A-lncRNAs) have been proven involving in regulating tumorigenesis, invasion and metastasis for a variety of tumors. The present study aims to screen lncRNAs with m6A modification, and investigate their biological signatures and prognostic values in kidney renal clear cell carcinoma (KIRC). Materials and Methods: lncRNA-seq profiles of KIRC samples and the clinical characteristics of corresponding patients were downloaded from the Cancer Genome Atlas (TCGA). The results of intersection of DElncRNAs and m6A-modified genes were analyzed by the weighted gene co-expression network analysis (WGCNA), to screen hub m6A-lncRNAs. Then, WGCNA was also used to construct a lncRNA-miRNA-mRNA (ceRNA) network. The Cox regression analysis was conducted on hub m6A-lncRNAs to construct the m6A-lncRNAs prognostic index (m6AlRsPI). The molecular signatures and prognosis for hub m6A-lncRNAs and m6AlRsPI were analyzed. The expression level of hub m6A-lncRNAs in KIRC cell lines were quantified by qRT-PCR. Results: A total of 21 hub m6A-lncRNAs associated with tumor metastasis were identified in the light of WGCNA. The ceRNA network for 21 hub m6A-lncRNAs was developed. The Cox regression analysis was performed on the 21 hub m6A-lncRNAs, screening two m6A-lncRNAs regarded as independent prognostic risk factors. The m6AlRsPI was established based on the two m6A-lncRNAs as follows: (0.0006066 * expression level of LINC01820) + (0.0020769 * expression level of LINC02257). KM survival analysis for m6AlRsPI shown the high m6AlRsPI group could contribute to higher mortality. The mutation and EMT analysis for m6AlRsPI showed the high m6AlRsPI group had more samples with gene mutation, more likely to occur EMT. Finally, GO and KEGG enrichment analysis were performed for mRNAs interacted with the two m6A-lncRNAs, showing they were involved in process of RNA splicing and regulation of mRNA surveillance pathway. qRT-PCR analysis shown the two m6A-lncRNAs were upregulated. Conclusion: In the present study, hub m6A-lncRNAs were determined associated with metastasis in KIRC. Two m6A-lncRNAs associated with overall survival were screened and m6AlRsPI was constructed and validated. Finally, the molecular signatures for m6AlRsPI and the two m6A-lncRNAs were analyzed to investigate the potential modulated processes in KIRC.